Is bony attachment necessary for dynamic reference frame in navigation-assisted minimally invasive lumbar spine fusion surgery?. Issue 1 (1st January 2019) - Lin, Hsi-Hsien; Lu, Yueh-Hsiu; Chou, Po-Hsin; Chang, Ming-Chau; Wang, Shih-Tien; Liu, Chien-Lin
Abstract: This study aimed to compare the accuracy of navigation-assisted percutaneous pedicle screw insertions between traditional posterior superior iliac spine (PSIS) fixed and cutaneously fixed dynamic reference frame (DRF) in minimally invasive surgery of transforaminal lumbar interbody fusion (MIS TLIF). This is a prospective randomized clinical study. Between May 2016 and Nov 2017, 100 patients who underwent MIS TLIF were randomly divided into bone fixed group (with PSIS fixed DRF) and skin fixed group (with cutaneously fixed DRF). The pedicel screws were inserted under navigational guidance using computed tomography (CT) data acquired intraoperatively with a Ziehm 3-dimensional fluoroscopy-based navigation system. Screw positions were immediately checked by a final intraoperative scan. The accuracy of screw placement was evaluated by a sophisticated computed tomography protocol. Both groups had similar patient demographics. Totally Five-hundred Twelve pedicle screws were placed in the lumbar spine. There were 2 moderate (2–4 mm) pedicle perforations in each group. The accuracy showed no significant difference between bone fixed and skin fixed DRF. There were no significant procedure-related complications. The skin fixed DRF provides similar accuracy in pedicle screw insertions with bone fixed DRF using intraoperative 3D image guided navigation in MIS TLIF. Skin fixed DRF not only serves as an alternative method but also saves a separate incision wound for bony attachment.